Ben Yokoyama and the Cookie of Perfection - Book 3 - Swanson, Matthew, 1974-; Behr, Robbi (New York : Alfred A. Knopf, 2021)
After getting a fortune cookie with the message, "Practice makes perfect," Ben meets new student Darby, who claims to be perfect and offers to teach Ben his secrets.
Ages 8-12.
Grades 4-6.
Keywords: Perfectionism (Personality trait) -- Fiction; Schools -- Juvenile fiction; Families -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Fortune cookies -- Juvenile fiction; Schools -- Fiction; Family life -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Fortune cookies -- Fiction